Perinatal Outcome and Change in Body Mass Index in Mothers of Dichorionic Twins: a Longitudinal Cohort Study - Simões, T (2013)
We used a prospective cohort to analyze the effect of change in BMI rather than change in weight, in mothers carrying dichorionic twins from a population that did not receive any dietary intervention. A total of 269 mothers (150 nulliparas and 119 multiparas) were evaluated. The average change (%) from the pre-gravid BMI was 7.2+/-6.1, 17.4+/-8.2, and 28.7+/-10.8, at 12-14, 22-25, and 30-34 weeks, respectively, without difference between nulliparas and multiparas. The comparison between maternities below or above the average change from the pregravid BMI failed to demonstrate an advantage (in terms of total twin birthweight and gestational age) of an above average change from the pregravid BMI, even when the lower versus upper quartiles were compared. Our observations reached different conclusions regarding the recommended universal dietary intervention in twin gestations. A cautious approach is advocated towards seemingly harmless excess weight gain, as normal weight women may turn overweight, or even obese, by the end of pregnancy, and be exposed to the untoward effects of obesity on future health and body image.